Effect of Adhesive Variation on the Characteristic of Palm Shells‘ Biomass Briquettes - Kholiq Deliasgarin Radyantho; Selvia Nur Qolbi; Faisal Manta; Doddy Suanggana; Muhammad Iskandar (Institut Teknologi Sepuluh Nopember, 2023)
Palm oil shells are an example of the residual products of the palm oil processing industry which can be utilized as a new alternative renewable energy source in the form of briquettes. The oil palm shells in this study were first carbonized for 1 hour with a heating temperature in the muffle furnace of 600˚C, then crushed and mashed, then kneaded with each variation of adhesive and molded so that the dough can form a cylinder with a diameter of 2 cm and 4 cm high. The average calorific value obtained for cornstarch adhesive, rice flour adhesive and pine resin adhesive were respectively 6634.29 cal/gr, 6702.47 cal/gr, and 7798.31 cal/gr. The average water content in cornstarch adhesive, rice flour adhesive, and pine resin adhesive were 5.1%, 5.0% and 3.7%, respectively. The average values of volatile matter content in the adhesives of cornstarch, rice flour, and pine resin were 30.90%, 31.70% and 60.73%, respectively. The results of this study indicate that any increase in the calorific value will be followed by a decrease in the water content and the varying values of the volatile matter content.